Generation of desminopathy in rats using CRISPR‐Cas9. Issue 5 (7th September 2020) - Langer, Henning T.; Mossakowski, Agata A.; Willis, Brandon J.; Grimsrud, Kristin N.; Wood, Joshua A.; Lloyd, Kevin C.K.; Zbinden‐Foncea, Hermann; Baar, Keith
Abstract: Background: Desminopathy is a clinically heterogeneous muscle disease caused by over 60 different mutations in desmin. The most common mutation with a clinical phenotype in humans is an exchange of arginine to proline at position 350 of desmin leading to p.R350P. We created the first CRISPR‐Cas9 engineered rat model for a muscle disease by mirroring the R350P mutation in humans. Methods: Using CRISPR‐Cas9 technology, Des c.1045‐1046 (AGG > CCG) was introduced into exon 6 of the rat genome causing p.R349P. The genotype of each animal was confirmed via quantitative PCR. Six male rats with a mutation in desmin ( n  = 6) between the age of 120–150 days and an equal number of wild type littermates ( n  = 6) were used for experiments. Maximal plantar flexion force was measured in vivo and combined with the collection of muscle weights, immunoblotting, and histological analysis. In addition to the baseline phenotyping, we performed a synergist ablation study in the same animals. Results: We found a difference in the number of central nuclei between desmin mutants (1 ± 0.4%) and wild type littermates (0.2 ± 0.1%; P  < 0.05). While muscle weights did not differ, we found the levels of many structural proteins to be altered in mutant animals. Dystrophin and syntrophin were increased 54% and 45% in desmin mutants, respectively ( P  < 0.05). Dysferlin and Annexin A2, proteins associated with membrane repair, were increased two‐fold and 32%, respectively, in mutants ( P  < 0.05). Synergist ablation caused similar increases in muscle weight between mutant and wild type animals, but changes in fibre diameter revealed that fibre hypertrophy in desmin mutants was hampered compared with wild type animals ( P  < 0.05). Conclusions: We created a novel animal model for desminopathy that will be a useful tool in furthering our understanding of the disease. While mutant animals at an age corresponding to a preclinical age in humans show no macroscopic differences, microscopic and molecular changes are already present. Future studies should aim to further decipher those biological changes that precede the clinical progression of disease and test therapeutic approaches to delay disease progression.